THE RURAL TOURISM AS A CATALYST: A DEEP DIVE INTO THE SYNERGY BETWEEN RURAL TOURISM AND POVERTY ERADICATION - Ramanayaka, Lathisha (Politeknik Pariwisata NHI Bandung, 2024)
This research critically examines the interplay between rural tourism and poverty alleviation in Sri Lanka, using an analytical framework based on secondary data analysis. By aggregating reports from institutions, the study employs empirical evidence and time-series data analyzed through econometric methodologies to explore this relationship. Pearson correlation and multiple regression analyses delineate the magnitude and directionality of the interconnection between the tourism sector and poverty reduction mechanisms. Correlation analysis evaluates inter-dependencies among variables, selecting significant ones for the regression model to enhance predictive capacity and minimize errors. Exhibit 3 presents Pearson correlation coefficients among these pivotal variables.The methodological framework is anchored in an empirical model derived from extensive literature review, positioning rural tourism development as the independent variable and poverty alleviation as the dependent variable. This model includes dimensions such as warfare impacts, economic growth trajectories, employment opportunities, and financial requisites for poverty mitigation, scrutinized through correlation and regression analyses.A key revelation is the multifaceted relationship between rural tourism and poverty alleviation, intricately linked with economic growth, political stability, and employment generation. While the direct linkage is modest, indirect connections through employment, infrastructure development, and political stability are significant. The research highlights these previously underexplored pathways, challenging conventional underestimations of socio-economic impacts of tourism. The findings advocate reconceptualizing rural tourism as an instrument for socio-economic transformation, addressing poverty challenges in rural contexts. The study critiques existing government poverty alleviation programmes, revealing gaps and inefficiencies. It argues for leveraging rural tourism within socio-economic frameworks, proposing a dual-strategy approach for policy implementation that emphasizes sustainable development and responsiveness to rural socio-cultural and environmental contexts.This research contributes to the discourse on sustainable rural development, positing rural tourism as a pivotal yet underutilized vector for socio-economic revitalization. The insights and recommendations extend beyond Sri Lanka, offering a blueprint for rural tourism-centered poverty alleviation strategies in the developing world.